1990
DOI: 10.1104/pp.93.2.479
|View full text |Cite
|
Sign up to set email alerts
|

Proton/Phosphate Stoichiometry in Uptake of Inorganic Phosphate by Cultured Cells of Catharanthus roseus (L.) G. Don

Abstract: Upon absorption of phosphate, cultured cells of Catharanthus roseus (L.) G. Don caused a rapid alkalinization of the medium in which they were suspended. The alkalinization continued until the added phosphate was completely exhausted from the medium, at which time the pH of the medium started to drop sharply toward the original pH value. Phosphate exposure caused the pH of the medium to increase from pH 3.5 to values as high as 5.8, while the rate of phosphate uptake was constant throughout (10-17 micromoles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 17 publications
5
76
0
2
Order By: Relevance
“…In the case of alix-1, lower vacuolar Pi levels and missorting of Pi transporters to the tonoplast may suggest that PHT1;1 proteins are exporting Pi out of the vacuole in mutant cells. In this scenario, acidification of the cytosol should be expected, as PHT1 proteins are Pi:H + symporters that cotransport two to four protons along with each Pi ion that is absorbed (Ullrich-Eberius et al, 1981;Sakano, 1990;Nussaume et al, 2011). Such changes in intracellular pH can be registered as variations in NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of alix-1, lower vacuolar Pi levels and missorting of Pi transporters to the tonoplast may suggest that PHT1;1 proteins are exporting Pi out of the vacuole in mutant cells. In this scenario, acidification of the cytosol should be expected, as PHT1 proteins are Pi:H + symporters that cotransport two to four protons along with each Pi ion that is absorbed (Ullrich-Eberius et al, 1981;Sakano, 1990;Nussaume et al, 2011). Such changes in intracellular pH can be registered as variations in NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, when the cells were suspended in unbuffered medium, we could follow the H+/Pi cotransport by measuring medium pH (15) by a miniature glass pH electrode well. Figure 2 shows Pi-induced changes in the pH of unbuffered medium and in fluorescence intensity of the cells.…”
Section: Cells Suspended In Unbuffered Mediummentioning
confidence: 99%
“…For the addition of Pi into a cuvette, a 10-mM solution of Na2HPO4 with a pH nearest to the medium pH (at the addition) was chosen from a series of solutions with pH ranging from 3.0 to 7.0 (pH interval 0.5, ref. 15).…”
Section: Measurement Of In Situ Bcecf Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the pH of the medium has a regulatory effect on nutrient uptake by the explant tissue (Hussey 1986). In the absence of pH regulation, the ionization of acidic and basic groups causes considerable changes in structure that affect their function at cellular level (Sakano 1990). Every species require optimum pH which promote maximum shoot formation.…”
Section: Discussionmentioning
confidence: 99%